Recipient screening in IVF: First data from women undergoing anonymous oocyte donation in Dublin - Salma Umme; Walsh David J; Marron Kevin D; Omar Ahmed B; Walsh Anthony PH; Sills E Scott (BMC, 2011)
Abstract Background Guidelines for safe gamete donation have emphasised donor screening, although none exist specifically for testing oocyte recipients. Pre-treatment assessment of anonymous donor oocyte IVF treatment in Ireland must comply with the European Union Tissues and Cells Directive (Directive 2004/23/EC). To determine the effectiveness of this Directive when applied to anonymous oocyte recipients in IVF, we reviewed data derived from selected screening tests performed in this clinical setting. Methods Data from tests conducted at baseline for all women enrolling as recipients (n = 225) in the anonymous oocyte donor IVF programme at an urban IVF referral centre during a 24-month period were analysed. Patient age at programme entry and clinical pregnancy rate were also tabulated. All recipients had at least one prior negative test for HIV, Hepatitis B/C, chlamydia, gonorrhoea and syphilis performed by her GP or other primary care provider before reproductive endocrinology consultation. Results Mean (±SD) age for donor egg IVF recipients was 40.7 ± 4.2 yrs. No baseline positive chlamydia, gonorrhoea or syphilis screening results were identified among recipients for anonymous oocyte donation IVF during the assessment interval. Mean pregnancy rate (per embryo transfer) in this group was 50.5%. Conclusion When tests for HIV, Hepatitis B/C, chlamydia, gonorrhoea and syphilis already have been confirmed to be negative before starting the anonymous donor oocyte IVF sequence, additional (repeat) testing on the recipient contributes no new clinical information that would influence treatment in this setting. Patient safety does not appear to be enhanced by application of Directive 2004/23/EC to recipients of anonymous donor oocyte IVF treatment. Given the absence of evidence to quantify risk, this practice is difficult to justify when applied to this low-risk population.